2014
DOI: 10.1515/pac-2013-1118
|View full text |Cite
|
Sign up to set email alerts
|

On the copolymerization of monomers from renewable resources: l-lactide and ethylene carbonate in the presence of metal alkoxides

Abstract: The copolymerization of l-lactide with ethylene carbonate carried out at 120 °C in the presence of organic derivatives of aluminum, zinc and tin as catalysts leads to the formation of linear polymers of relative molecular masses in the 10 000-30 000 range containing up to 12 mol. % of carbonate monomeric units (m.u.). A decrease in T g of copolymers down to 48 °C demonstrates the internal plasticization effect for polylactide matrix. In the first reaction step mainly lactide homopolymerization proceeds in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…Generally, the observed T g of the PLA phase in the systems initiated with PG 8 , MPG 8 and PG 18 was slightly lower (44-52 ∘ C) than that presented in the literature 15 for linear PLA homopolymers (approximately 62 ∘ C). This reflects the internal plasticization of PLA with flexible PG cores characterized by T g in the range −36 to −47 ∘ C. Moreover, in three cases, a second T g , characteristic for the PG domains, was determined, which suggests that oligoglycerols exhibit only partial miscibility with PLLA.…”
Section: Syntheses Of Multi-arm Pla In Model Research Installationcontrasting
confidence: 61%
See 3 more Smart Citations
“…Generally, the observed T g of the PLA phase in the systems initiated with PG 8 , MPG 8 and PG 18 was slightly lower (44-52 ∘ C) than that presented in the literature 15 for linear PLA homopolymers (approximately 62 ∘ C). This reflects the internal plasticization of PLA with flexible PG cores characterized by T g in the range −36 to −47 ∘ C. Moreover, in three cases, a second T g , characteristic for the PG domains, was determined, which suggests that oligoglycerols exhibit only partial miscibility with PLLA.…”
Section: Syntheses Of Multi-arm Pla In Model Research Installationcontrasting
confidence: 61%
“…The thermal properties of the multi‐arm star PLLA crude products were characterized by means of DSC with respect to the glass transition temperatures ( T g ) and the presence of a crystalline fraction ( x ) (Table ). Generally, the observed T g of the PLA phase in the systems initiated with PG 8 , MPG 8 and PG 18 was slightly lower (44–52 °C) than that presented in the literature for linear PLA homopolymers (approximately 62 °C). This reflects the internal plasticization of PLA with flexible PG cores characterized by T g in the range −36 to −47 °C.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It should be noted that the thermodynamic products of the reaction between CO 2 and epoxides are five-membered cyclic carbonates (1,3-dioxolan-2-ones) that are easily available in the presence of the appropriate catalysts. They cannot be applied as precursors for poly(alkene carbonates) due to the positive Gibbs free enthalpy of polymerization [12]; however, it has been found that some of them could undergo copolymerization with heterocyclic monomers [13,14]. Unfortunately, in most of the studied systems, the amount of carbonate units incorporated into the polymer chain was small.…”
Section: Introductionmentioning
confidence: 99%